Trajetórias de egressos: a formação em educação popular na perspectiva da aprendizagem ao longo da vida - Barbosa, Sanya Teles (2024)
This dissertation analyze the trajectories of graduates of the doctoral course in Education at UFPB in the Popular Education line. The research question is: what are the trajectories of graduates of the doctoral course in Popular Education at PPGE in their educational, social, and professional activities? Additionally, how does this population evaluate the quality of training for the acquisition of new learning, as well as the most and least highlighted aspests of this training for the acquisition of new learning, as well as the most and least highlighted aspects of this training for the acquisition of material and immaterial benefits? These objectives addressed the identified issues both theoretically and methodologically: (i) The aim of this study is to examine the social, educational, and professional trajectories of graduates from the Popular Education line of the Postgraduate Program in Education at the Federal University of Paraíba. (ii) Additionally, this study seeks to evaluate the material and immaterial benefits of this doctoral training, based on the theoretical perspective of lifelong learning/ education. (iii) Finally, this study aims to determine whether there is a correlation between the social, educational, and professional performances of graduates and the proposals of the Popular Education line. To accomplish this, we began with the assumption that doctoral training offers its graduates both tangible and instangible advantages, such as increased socialization and preparation for the workforce. This qualitative study utilized two data collection methods: semi- structured interviews (questionnaire) and group interviews (focus group). Thirteen (13) PhD graduates (10 women and 3 men) responded to the questionnaires applied via Google Forms, corresponding to just over 36% of graduates in the period 2017 to 2021. The graduates identified professional advancement and qualification, entry into higher education, salary progression, and increased learning as contributions to their doctoral training in popular education. Of the thirteen graduates interviewed, eight (8) participated in the round table discussion. They discussed issues related to training and lifelong learning. The study concluded that doctors understand the complementary nature of lifelong learning and popular education, from an educational perspective that encompasses all aspects of their lives. The reports noted that training in popular education yielded both material and immaterial benefits.